Effect of System Frequency on Fuel at Peak Load MTU 12V 2000 G Engine 62 Units of PLTD Biduk-Biduk - Eka Mahdi Ananta; Anis Siti Nurrohkayati (Procedia of Engineering and Life Science, 2022)
The demand for electrical power in the Biduk-Biduk sub-district increases in population and the use of electronic devices as primary needs and other devices that create excess power at peak loads. This greatly affects the use of less efficient fuel. The purpose of this study was to determine the frequency of the system on the fuel consumption of the MTU 12V 2000 G 62 engine at PT. PLN (Persero) PLTD Biduk-Biduk unit. The method of collecting data is through direct field observation by conducting interviews and clear observations and recording the facts of the data observed in the field. frequency increase to 50.20 HZ to keep the increase in usage or shock load from consumer usage. The average usage in January 2022 with a total operating hours of 161 hours on the MTU 12V 2000 G 62 engine is 0.29021 /kWH. The average percentage of fuel use in the average use of Sfc in January 2022 is 0.0989%/kWH.